Graphene: A Multifunctional Nanomaterial with Versatile Applications - H. C. Ananda Murthy; Suresh Ghotekar; B. Vinay Kumar; Arpita Roy (Advances in Materials Science and Engineering)
Graphene is a 2D material of high quality obtained from a single atom with unique electronic properties. Graphene has the potential to improve the efficiency, versatility, and durability of a wide range of materials and their applications, but its commercial exploitation will require further study. Due to its flatness and semiconductivity in addition to its high surface area, high mechanical rigidity, high thermal stability, superior thermal conductivity, and electrical conductivity, good biocompatibility, and easy functionalization, graphene is the best candidate for multifunctional applications which opened up new possibilities for potential devices and systems. Every type of graphene material is found to exhibit different and unique tunable properties. Graphene is the best candidate in making nanocomposite-based electrochemical sensors. Graphene is among the best electronic materials, but synthesizing a single sheet of graphene has received less attention. The objective of this chapter is to bring awareness to readers on the synthesis, properties, and applications of graphene. The limitations of the current knowledge base and prospective research directions related to graphene materials have also been illustrated.